Aerosols and hydrocarbons in the atmosphere of a white dwarf planet - Ryan J. MacDonald; Christopher E. O’Connor; Victoria A. Boehm; E. M. May; David K. Sing; Elijah Mullens; L. C. Mayorga; Trevor O. Foote; Simon Blouin; Logan A. Pearce; Nikole K. Lewis; Jeff Valenti; et al. (Nature, 2026)
Abstract Most stars, including our Sun, will one day evolve into red giants and, subsequently, white dwarfs. Several planet candidates have recently been identified orbiting white dwarfs 1–4 , demonstrating that planets can survive the stellar post-main-sequence stage intact. Little is known about the atmospheric composition of post-main-sequence planets, with the most evolved transiting planets with atmospheric detections so far orbiting subgiants 5,6 . Here we report an atmospheric detection for the white dwarf planet WD 1856 b, achieved through transmission spectroscopy with the James Webb Space Telescope (JWST) Near-Infrared Spectrograph (NIRSpec) PRISM. Our 0.5–5.0-μm spectrum reveals the presence of hydrocarbons (odds ratio of 167:1–5,377:1, with CH 4 preferred at 17:1–30:1), aerosols (2 × 10 5 :1–2 × 10 6 :1) and thermal emission from the planetary nightside (2 × 10 63 :1–2 × 10 73 :1). Our spectral analysis constrains the mass of WD 1856 b to 4.3–10.9 M J , finds a carbon-enriched atmosphere (with a CH 4 abundance of approximately 7%) and an effective temperature exceeding the expected planetary equilibrium temperature (390–412 K versus 160 K). On the basis of cooling models, these results indicate that WD 1856 b underwent a migration-related reheating event 3.0–5.5 Gyr into the white dwarf phase, consistent with post-main-sequence tidal evolution to the present-day 0.02- au circular orbit. Our results provide a window into the ultimate fate of giant planets orbiting stars with masses similar to our Sun.